2021
DOI: 10.1364/boe.443066
|View full text |Cite
|
Sign up to set email alerts
|

Refractive-index matching enhanced polarization sensitive optical coherence tomography quantification in human brain tissue

Abstract: The importance of polarization-sensitive optical coherence tomography (PS-OCT) has been increasingly recognized in human brain imaging. Despite the recent progress of PS-OCT in revealing white matter architecture and orientation, quantification of fine-scale fiber tracts in the human brain cortex has been a challenging problem, due to a low birefringence in the gray matter. In this study, we investigated the effect of refractive index matching by 2,2’-thiodiethanol (TDE) imme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…We applied refractive index matching to our samples to increase the SNR in the PS-OCT measurements. Previously, we showed that index matching significantly improved the SNR and subsequentially enhanced the accuracy of in-plane orientation and apparent birefringence measurements 21 . It is important to note that, without index matching, the limited SNR in the data would prevent the successful application of our orientation estimation from the two illumination measurements.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We applied refractive index matching to our samples to increase the SNR in the PS-OCT measurements. Previously, we showed that index matching significantly improved the SNR and subsequentially enhanced the accuracy of in-plane orientation and apparent birefringence measurements 21 . It is important to note that, without index matching, the limited SNR in the data would prevent the successful application of our orientation estimation from the two illumination measurements.…”
Section: Discussionmentioning
confidence: 92%
“…We cut two blocks in the corpus callosum region from one of the MGH samples and one coronal slab from the other MGH sample. We applied refractive index matching to all the samples by incubations in 2,2-thiodiethanol solutions as described in our previous work 21 . The ex vivo imaging procedures are approved by the Institutional Review Board of the MGH.…”
Section: D Orientation Reconstruction Algorithmmentioning
confidence: 99%
“…All of these issues do not appear when ex vivo tissue images are merged because excised tissue would normally be imaged either through a glass slide or in a bath with refractive index matching fluid. 39 Index matching is not feasible during surgery because any additional liquid in the surgical pocket is contaminated with red blood cells which in turn significantly degrade the OCT scan quality due to excessive scattering and water absorption. Despite our best effort to remove excessive liquid pooling in the nerve holder channel after the rehydration, some of our acquired volumes suffered signal degradation due to liquid trapped in the meniscus between the nerve and the prisms.…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been previously demonstrated by other groups to remove OCTA tail artifacts, 37 , 38 which could be applied prior to merging OCTA volumes. All of these issues do not appear when ex vivo tissue images are merged because excised tissue would normally be imaged either through a glass slide or in a bath with refractive index matching fluid 39 . Index matching is not feasible during surgery because any additional liquid in the surgical pocket is contaminated with red blood cells which in turn significantly degrade the OCT scan quality due to excessive scattering and water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Image Acquisition and Postprocessing-Scattering and Birefringence Fitting: Extraction of scattering coefficient, [71,74] back-scattering coefficient, and birefringence [30] followed previously reported methods, by fitting the depth profiles of PSOCT intensity and retardance.…”
Section: Methodsmentioning
confidence: 99%